The effect of body markers on golf driving performance - Kenny, I.; Anderson, R. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
No study to date has reported if and how the use of body markers used in three dimensional optical tracking methods to study swing kinematics in golf affect movement performance. Egret et al. (2004) studied the use of wired electromyographic equipment during the golf swing and concluded that the equipment significantly influenced the kinematic pattern of the golf swing. Researchers have previously concentrated their methodological analyses on such factors as the type of marker used, either wand or skin marker (Kirtley, 2002) or skin movement artefact during movement (Holden et al., 2007). The golf swing is a movement that is closed-chain, non-impact and does not cause excessive unwanted movement of skin and wand markers. It is therefore concluded that the golf swing lends itself well to kinematic analysis using body markers. The aim of the present study was to evaluate the effect of body markers on golf driving performance for tests carried out in a laboratory setting.